Effect of an Educational Program on Nurses' Knowledge about Pediatric Cardiopulmonary Resuscitation in Mosul City Hospitals - Mohammed Attallah Ahmed; Faris Bakir Al-Sawaf (College of Nursing,University of Mosul, 2016)
Background and aim: It is very important that the nurse develop the required knowledge that allows them to assess the patients in emergency situations and perform pediatric cardiopulmonary resuscitation (CPR) when needed both inside and outside hospitals together with the use of the appropriate and correct methods. The purpose of this study is to assess the effect of an educational program on nurses' knowledge about pediatric CPR and determine relationship between nurses' knowledge and demographic information (gender, age, educational level, years of employment, place of work). Materials and method: A Quasi-experimental study was carried out in Ibn Al-Atheer teaching hospital(study group) and Al-Khansaa Teaching Hospital(control group) in Mosul city from October 28th 2013 to31 December 2014. The study sample was selected randomly consisting of 60 nurses from both hospitals after taking their consent, and the sample was divided into two groups, the study group (30) nurses in Ibn Al-Atheer Teaching Hospital, and the control group (30) nurses in Al-Khansaa Teaching Hospital. (39 male and 21 female).Statistical Package for the Social Science (SPSS), Frequency, Mean, t-test, and ANOVA-one way test was used for data analysis. Results:The results showed also that the presence of statistically highly significant differences in the knowledge of nurses after implementation of the educational program about pediatric CPR compared to their knowledge in the period preceding the implementation of the program in the study group. The study concluded that the existence of a clear and significant correlation between knowledge about pediatric CPR among nurses and the majority of the demographic characteristics. Conclusion: the presence of a significant lack in the knowledge of nurses about pediatric CPR before application educational program. Recommendations: The study recommends, preparation, development and implementation of such educational programs in all other Iraqi hospitals. Keywords: Effect ,educational program, cardio pulmonary resuscitation